Integrasi Fitur Linguistik, Paralinguistik, dan Ekstralinguistik dalam Kualitas Interpretasi Ritual “Tetek Pantan” Suku Dayak Ngaju di Pemerintahan Kalimantan Tengah - Natalia, Febrina (Jurnal Penerjemahan, 2018)
The Government of Central Kalimantan Province has a singular tradition in welcoming official government guests or delegations. This traditional ritual of the Dayak Ngaju is well-known as “Tetek Pantan”, which symbolizes the cordiality and honor accorded by the Bumi Tambun Bungai – a historical name given to the Central Kalimantan Province and its people – to its visiting guests. This ritual is performed for guests who set foot for the first time in Central Kalimantan Province. Therefore, it will not be performed twice for the same persons on their successive visits. This ritual is led by a Damang or Mantir Adat (Customary Leader) of the Dayak Ngaju in the local Dayak Ngaju language. Therefore, an interpreter assumes a crucial role in delivering the message of the Damang/Mantir Adat from the local language to the the target language (English) of the audience (guests). In this manner, the original message of the speaker can be accurately conveyed to the audience. In this respect, such an interpreter must have the necessary competence and skill to speak as well as to understand the local Dayak Ngaju language. Otherwise, the communication between the speakers will not proceed smoothly. Viewed from the perspective of language as a communication tool, the results of this study demonstrate that the quality of interpretation in this ritual does not merely depend on linguistic features (vocabulary and grammar), but it is also greatly influenced by paralinguistic features (pronunciation, articulation, intonation). In addition to those features, message accuracy should take into account extralinguistic features such as: specialized knowledge, ethnic background, noise, gestures and eye contact which also build strong effects towards the oral interpretation quality. Key words: interpretation, linguistics, paralinguistics, extralinguistics.